2008
DOI: 10.1152/ajpregu.00908.2007
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerves and nNOS: roles in natriuresis of acute isovolumetric sodium loading in conscious rats

Abstract: Kompanowska-Jezierska E, Wolff H, Kuczeriszka M, Gramsbergen JB, Walkowska A, Johns EJ, Bie P. Renal nerves and nNOS: roles in natriuresis of acute isovolumetric sodium loading in conscious rats. Am J Physiol Regul Integr Comp Physiol 294: R1130-R1139, 2008. First published January 30, 2008 doi:10.1152/ajpregu.00908.2007.-It was hypothesized that renal sympathetic nerve activity (RSNA) and neuronal nitric oxide synthase (nNOS) are involved in the acute inhibition of renin secretion and the natriuresis followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Recent studies in conscious rats may provide suggestions in this regard. Renal denervation did not affect the renin inhibitory or natriuretic responses to a sodium load (50 mol⅐kg Ϫ1 ⅐min Ϫ1 ), which elicited a slight increase (5)(6)(7)(8) in MAP (21), compatible with the notion that RSNA plays only a minor role when MAP increases measurably. However, preliminary results have shown 1) that a lower infusion rate (20 mol⅐kg Ϫ1 ⅐min Ϫ1 ), which did not change MAP, nevertheless reduced RSNA (measured by implanted electrodes) and 2) that the natriuresis induced by this sodium load was eliminated by renal denervation (7).…”
Section: Natriuretic Mechanismssupporting
confidence: 65%
“…Recent studies in conscious rats may provide suggestions in this regard. Renal denervation did not affect the renin inhibitory or natriuretic responses to a sodium load (50 mol⅐kg Ϫ1 ⅐min Ϫ1 ), which elicited a slight increase (5)(6)(7)(8) in MAP (21), compatible with the notion that RSNA plays only a minor role when MAP increases measurably. However, preliminary results have shown 1) that a lower infusion rate (20 mol⅐kg Ϫ1 ⅐min Ϫ1 ), which did not change MAP, nevertheless reduced RSNA (measured by implanted electrodes) and 2) that the natriuresis induced by this sodium load was eliminated by renal denervation (7).…”
Section: Natriuretic Mechanismssupporting
confidence: 65%
“…(Kompanowska-Jezierska et al, 2008;Wainford et al, 2013). Following the 2 h recovery period, conscious rats were challenged with an acute 1 M NaCl infusion protocol consisting of a 1 h control period (isotonic saline, 20 µl min −1 , I.V.)…”
Section: Acute 1 M Nacl Sodium Infusionmentioning
confidence: 99%
“…In addition, it was shown that the natriuresis in response to sodium load, which increased blood pressure, was inhibited by the administration of ANG II, suggesting that a decrease in the RAS is a prerequisite for the natriuretic response to sodium load (21, 74). Subsequent elegant studies in humans and laboratory animals further suggest that the suppression of renin release in response to an acute modest sodium load is not only independent of changes in blood pressure, but also independent of cardiac output, GFR, ANP, ␤ 1 -adrenergic receptors, plasma sodium levels, osmolality, renal nerves, and nNOS-derived NO (73,456,593,717). Therefore, the question arises which mechanism(s) mediates natriuresis and suppression of renin in response to an acute modest sodium load.…”
Section: B Salt Intakementioning
confidence: 99%